Allergic reaction to platelet-rich plasma (PRP): Case report. Issue 10 (March 2019) - Latalski, Michal; Walczyk, Alicja; Fatyga, Marek; Rutz, Erich; Szponder, Tomasz; Bielecki, Tomasz; Danielewicz, Anna
Abstract: Rationale: In the recent years, growing interest is focused on the use of platelet-rich plasma (PRP) in wound healing and tissue regeneration. There are a number of papers regarding the usefulness of PRP in the healing of ulcerations, skin injures, bone loss or distraction osteogenesis. Most authors emphasize the safety of PRP usage due to its authogenic nature. Patient concerns: We present a case of a 14 -year-old boy admitted to our department due to simple bone cyst of the distal tibia, qualified for injection of PRP into the cyst. PRP was separated with the use of Magellan Autologous Platelet Separator System (Arteriocyte Medical Systems Hopkington, MA) according to the manufacturers' manual. Immediately after separation during short-term IV anaesthesia, 3 mL of PRP was installed to the bone cyst under image intensifier control. Diagnoses: Within the first 24 hours after exposure to PRP, the skin rash appeared. Physical examination revealed the small red papular, regionally purpuric eruptions, mainly concentrated on the upper extremities and on more warmed regions of skin, in association with pharyngitis, tonsillar enlargement, mucopurulent discharge in the posterior pharynx and swelling of the eyelids. Interventions: As the patient received calcium citrate with the PRP injection additional calcium citrate test were performed. Skin prick testing (negative) was and an intradermal test was positive (10×13 mm). Treatment included Claritine (Loratidinum) and Clemastin (Clemastinum)—both antihistaminic drugs. Outcomes: All symptoms withdrew and the patient was released home after 4 days. The patient is in 6 years follow-up without any symptoms of allergic disease. Lessons: Our case shows that safety of use of PRP is not absolutely sure. The pure autologous tissue is safe, but preparation for its use can substantially decrease this safety. In our patient, only limited skin reaction to calcium citrate was observed, but general reaction leading to anaphylactic shock cannot be excluded. In order to reduce the risk of side effects skin test should be performed but as there were no records of allergic diseases on family and patients medical history this should apply to all patients.